Investigating the therapeutic potential of adult mouse cerebellum derived neural stem cells and the morphological characterisation of extracellular vesicles - Nizamudeen, Zubair Ahmed (2019)
Neural stem cells (NSCs) in the adult mammalian brain have been identified in the sub-ventricular zone (SVZ) of the lateral ventricles (LV) and the sub-granular zone (SGZ) of the hippocampus. Recently, the Bergmann glia (BG) of the adult mammalian cerebellum have been proposed as a NSC population of the adult brain. However, their regenerative potential is largely unclear. This project aims to investigate the properties of LV-derived and cerebellum-derived NSCs from the adult mouse brain by developing and optimising protocols to (a) differentiate primary NSCs, and (b) characterise extracellular vesicles (EV) secreted by NSCs.